MATHEMATICAL MODEL OF COMPARATOR WITH REGULATED SENSITIVITY FOR FAST ACTING MULTIBIT WEIGHT REDUNDANCY ADC - Azarov, Alexey; Reshetnik, Alexandr (Scientific Works of Vinnytsia National Technical University, 2015)
Mathematical model of comparator with regulating sensitivity for fast multidigit ADC with weight redundancy is suggested